Interplay of health literacy, healthcare access and health behaviors with oral health status among older persons - Amoah, Padmore Adusei; Boateng, Millicent Ofori; Koduah, Adwoa Owusuaa; Acheampong, Princess Ruhama (Frontiers in Public Health, 2022)
This study contributes to the ongoing debate on social determinants of oral health of older persons. Specifically, it examines the direct and indirect effects of health literacy and access to healthcare on oral health status of older persons. The study also investigates whether general health status and health behaviour (specifically, routine medical check-ups) explain the association of health literacy and healthcare access with oral health status. The gender dimensions of these relationships are also explored. Data were derived from 522 participants aged 50 years and older located in five regions in Ghana. Path analyses in structural equation modelling (SEM) were used to analyse the data. General health status (β = -0.049, p<0.005), medical check-up (β = 0.124, p< 0.01), and health literacy (β= 0.133, p< 0.01) were positively associated with oral health status. General health status mediated the positive relationship between health literacy and oral health status (β = 0.048, p<0.01). General health status (β = 0.016, p<0.05) and medical check-ups (β = 0.025, p<0.05) mediated the association between access to healthcare and oral health status. The mediational role of routine medical check-up in the association between access to healthcare and oral health status was significantly stronger (B = 0.063, p< 0.01) among men (β = 0.051, p< 0.01) than women (β = 0.003, p > 0.05). Analyses of oral health issues among older persons in Ghana and settings alike must recognise the complex interplay among critical social determinants to initiate pragmatic health and social policy interventions.